The Empowering the Elderly: Psychoeducation as an Effort to Prevent Loneliness - Pangesti, Ary Tri Rahayu; Nurhamida, Yuni (Research Psychologie, Orientation et Conseil, 2024)
The elderly population in Malang City is projected to reach 114,334 individuals, presenting various challenges related to health, cognitive function, and socio-emotional well-being. This study explores the role of psychoeducation in preventing loneliness among the elderly. According to Erik Erikson's theory, elderly individuals face the stage of "Integrity versus Despair," where successful navigation leads to life satisfaction, while failure results in hopelessness. Loneliness, exacerbated by reduced social roles and interactions, negatively impacts mental and physical health. Psychoeducational interventions aim to enhance understanding and provide coping strategies to address loneliness. This research, conducted in RT 02 Losari, Malang, utilized a quasi-experimental design with pretest and posttest measurements on 18 elderly participants. Data collection involved interviews and observations, highlighting limited social support and interaction among the elderly. The results demonstrated a significant increase in knowledge about loneliness, with the pretest average score of 70.56 improving to 86.11 post-intervention. The paired t-test confirmed the effectiveness of psychoeducation in reducing loneliness. Discussion emphasizes the importance of integrating psychological and educational aspects to enhance social skills, cognitive restructuring, and stress management. Recommendations include developing elderly-friendly community programs, leveraging technology for remote interventions, and fostering multidisciplinary approaches to improve mental health care access for the elderly. Future research should focus on expanding psychoeducational interventions and involving families and social environments to promote positive interactions and support for the elderly.